Trustworthy computing and services : International Conference, ISCTCS 2014, Beijing, China, November 28-29, 2014, Revised selected papers /: International Conference, ISCTCS 2014, Beijing, China, November 28-29, 2014, Revised selected papers. (2015) - Unknown
No abstract available